Simmental cattle are effective methods of intensive treatment of purulent inflammatory processes of the fingers and toes (Eurasian Medical Research Periodical, 2022)
For the intensive treatment of purulent inflammation of the fingers and hooves in cattle of Simmental breed, effective treatment of intravenous and enrofloxacin 10% antibiotic with intravenous and butasal-100 + sodium chloride 0.9% solution + ascorbic acid, which acts as a bio-stimulant method was developed and treatment duration was reduced to 7 days compared to the control group